2020
DOI: 10.1002/glia.23956
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the glutamate transporter 1 is regulated by laforin and malin: Implications in Lafora disease

Abstract: Lafora disease (LD) is a fatal rare type of progressive myoclonus epilepsy that appears during early adolescence. The disease is caused by mutations in EPM2A or EPM2B genes, which encode laforin, a glucan phosphatase, and malin, an E3‐ubiquitin ligase, respectively. Although the exact roles of laforin and malin are still not well understood, it is known that they work as a complex in which laforin recruits targets that will be ubiquitinated by malin. Recently, we suggested that the type of epilepsy that accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Successfully, Muñoz-Ballester et al [ 23 ] unravelled a decreased level of glutamate transporter GLT-1 at the plasma membrane of LD astrocytes, which might underlie the in vivo glutamate clearance defects present in LD mouse models [ 24 ]. Furthermore, Perez-Jimenez et al [ 25 ] confirmed that such defective alterations are related to insufficient ubiquitination of GLT-1 due to the absence of a functional laforin/malin complex. On the basis of these strong data, it became clear that an altered excitatory glutamatergic system might be behind the sensitivity to convulsant agents observed in LD mouse models [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Successfully, Muñoz-Ballester et al [ 23 ] unravelled a decreased level of glutamate transporter GLT-1 at the plasma membrane of LD astrocytes, which might underlie the in vivo glutamate clearance defects present in LD mouse models [ 24 ]. Furthermore, Perez-Jimenez et al [ 25 ] confirmed that such defective alterations are related to insufficient ubiquitination of GLT-1 due to the absence of a functional laforin/malin complex. On the basis of these strong data, it became clear that an altered excitatory glutamatergic system might be behind the sensitivity to convulsant agents observed in LD mouse models [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, impaired K + and glutamate clearance, as seen above, can lead to neuronal hyperexcitability and contribute to epileptogenesis. In this regard, in addition to the aforementioned data on EAAT2 [ 52 , 53 , 54 ], we recently observed the upregulation of the astrocytic Kir4.1 channel in a new laforin-deficient zebrafish model [ 14 ]. The downregulation of this channel has generally been described in inflammatory states, but impaired function of Kir4.1 has also been associated with autism–epilepsy phenotypes in humans [ 127 ], and we therefore cannot exclude a possible role for it in the epileptic phenotype observed in epm2a KO larvae.…”
Section: Resultsmentioning
confidence: 76%
“…Five additional studies were selected by checking the references of the identified relevant papers. A total of 35 studies were then identified for inclusion in the current review [ 10 , 12 , 14 , 18 , 21 , 22 , 23 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successfully, Muñoz-Ballester et al [23] unraveled a decreased level of glutamate transporter GLT-1 at the plasma membrane of LD astrocytes, which might underlie the in vivo glutamate clearance defects present in LD mouse models [24]. Furthermore, Perez-Jimenez et al [25] con rmed that such defective alterations are related to insu cient ubiquitination of GLT-1 due to the absence of a functional laforin/malin complex. On the strength of these data, it became clear that an altered excitatory glutamatergic system might be behind the sensitivity to convulsant agents observed in LD mouse models [26], [27].…”
Section: Introductionmentioning
confidence: 99%